Analysis Approach Development of Transport Phenomena for Engineers in Industry: basic concepts and advanced solving techniques - Edali, Mohamed; Milad, Asma; Alaswad, Walid; Bseibsu, Ali; Sahem, Zaed; Rajeb, Faraj Ben; Elkamel, Ali (Journal of Pure & Applied Sciences, 2021)
Applied Mathematical representation Phenomena Sciences in Engineering development is related to the knowledge advances of diﬀerent areas of Chemical Engineering and other engineering ﬁelds. The advances in mathematical analysis and the computer tools in Transport Phenomena help solve complex problems involving momentum, heat, and mass transfer. Transport Phenomena applied to the engineering teaching process presents unique challenges regarding the complexity of biological material and how it changes during the application of diﬀerent transformation or preservation treatments. Therefore, studying the basic concepts of Transport Phenomena and their applications to analyze, predict, and design any process is essential in advancing industrial Engineering. This paper presents some of those fundamental concepts of recent applications and research orientations. Several critical elements of numerical analysis are profiled in COMSOL Multiphysics with 0-D, 1-D, 2-D, and 3D models. These elements are root-finding, ordinary and partial differential equations, and linear system analysis. These methods underly nearly all problem-solving techniques by numerical analysis for chemical engineering applications. COMSOL Multiphysics is illustrated concerning some typical applications in chemical engineering.